THE EFFECTS OF OSTEOPATHIC TREATMENT ON COMMON FEMORAL ARTERY BLOOD FLOW AND SKIN TEMPERATURE IN SPINAL CORD INJURED AND ABLE-BODIED INDIVIDUALS - Murray, David J.G. (My University, 2014)
ABSTRACT
Individuals with spinal cord injuries (SCI) are prone to significant alterations in vascular structure and function. This study was designed to examine the effects of osteopathic treatment on mean leg (MLBF) blood flow and skin temperature in the lower extremities of individuals with chronic SCI compared to able-bodied (AB) individuals. Methods: Nine individuals (age 44 ± 17.5 years) with a chronic SCI (C6-T12; AIS A-B; 3.7 ± 4.6 years post-injury) and six AB individuals (38.3 ± 9.7 years) participated. The protocol consisted of 1 interview session and 3 osteopathic treatment sessions. Doppler ultrasound measured the diameter and mean blood velocity in the CFA before (Pre) and after (Post) each session. Skin temperatures were measured using skin thermistors at three different sites on the left leg. Change scores were calculated and measured as post-treatment minus pre-treatment. Results: A two-way ANOVA revealed an increase in flow of 16±2 ml/min within the SCI group and a decrease in flow of 25±2 ml/min in the AB group (p = 0.04). There was also a smaller reduction in skin temperature in individuals within the SCI versus AB (left thigh: SCI, -0.5±0.2° C; AB, -1.2±0.2°C, p(left foot: SCI, -0.1±0.4°C; AB, -1.8±0.4°C, pAll treatments resulted in small increases in MLBF in the SCI group versus small decreases in the able-bodied group and smaller skin temperature decreases in the SCI versus the decreases in the AB group, potentially indicating reduced skin temperature reactivity. These findings emphasize the potential for different physiological responses to interventions in individuals with SCI compared to AB individuals.
Keywords: Spinal Cord Injuries; Osteopathy; Blood Flow; Common Femoral Artery; Skin Temperature; Alternative and Complementary Medicine; Alternative and Complementary Medicine